The Effect of Forced Exposure to Crosscutting Information: What Is the Effect of Broadcast News Shows That Deliver Opposing Opinions? - Sangik Han; Sungjoong Kim (Asian Journal for Public Opinion Research)
News shows often deliver crosscutting information to their audiences by inviting commentators from rival political parties. If these news shows foster the formation of informed and balanced views of the audience, mass media could provide countermeasures against political polarization. To test the effect of such news shows, this study conducted an experiment with two variants of a simulated radio talk show. In the partisan scenario, the two guest commentators’ affiliations suggested their ideological orientation. In the non-partisan scenario, the commentators had neutral affiliations. We divided participants into two ideology groups, liberals and conservative, and compared each group’s evaluation of the commentators in the two scenarios. Two multivariate analysis of variance (MANOVA) tests were conducted to analyze the effect of the perceived ideology of the commentators on respondents’ attitudes toward the commentators’ arguments depending on their own ideological inclinations. The analyses results did not support the hypothesis that anticipated partisan attitudes towards the commentators’ arguments. It was only the liberal respondents who showed statistically significant different attitudes toward commentators’ arguments in each of the two scenarios. The findings suggest that such broadcast shows do not automatically trigger partisan message processing and may help the audience to develop informed and balanced opinions. While the current study failed to find conclusive evidence to support the hypotheses, it also found that the perceived ideology of the information source may trigger partisan attitudes for certain types of issues. Future studies with different experiment designs are needed to investigate the issue further.